Libri e Artigiani del Libro: Le Raccomandazioni dei Giuristi Musulmani (XIV Secolo) - Canova, Giovanni (Journal of Arabic and Islamic Studies, 2017)
The paper deals with the comments 14th-century jurists, Ibn Jamāʿa, Ibn al-Ḥājj and al-Subkī made about books and bookmaking, which highlight their ambivalent attitude towards the craftsmanship of those involved in the production of books. While extolling the merits of papermakers, scribes and bookbinders in connection with the production of religious books, the jurists urged these craftsmen to proceed in strict compliance with the Islamic code. Copying and binding certain kinds of books, such as folk romances, was severely censured or even prohibited. Some suggestions aiming at the prevention of fraud and illicit behaviour were also included in sections of legal treatises dealing with the crafts of book-production.